Social desirability bias in qualitative health research - Bispo Júnior, José Patrício (Revista de saúde pública, 2022)
The objective of this essay is to discuss the social desirability bias in qualitative health research. The social desirability bias consists of a systematic research error, in which the participant presents answers that are more socially acceptable than their true opinions or behaviors. Qualitative studies are very susceptible to this type of bias, which can lead to distorted conclusions about the studied phenomenon. Initially, I present the theoretical-conceptual aspects of the social desirability bias. I discuss how its occurrence can be intentional or unintentional, with a distinction between the concepts of self-deception and impression management. Then, I discuss the determining factors of this bias from four dimensions: study design; study context; interviewee's characteristic; interviewer's posture. Finally, I present a systematization of six strategies to be used by qualitative researchers for identifying and controlling social desirability bias.